O uso de palmilhas versus fortalecimento da musculatura intrínseca do pé no tratamento da fasciite plantar: uma revisão sistemática - Souza, Thiago Melo Malheiros de [UNIFESP] (2020)
Introduction: The foot is composed by active, passive, and neural structures. The medial longitudinal arch (MLA) is held by the interaction of these components and the intirinsic foot muscles (IFM) has an important part on this process. In recent years it is been observed a relation between the weakness of the IFM and plantar fasciitis (PF). PF is defined as an inflammatory process at the fascia. Its symptoms are pain on the plantar fascia, especially on the first steps in the morning and palpation of the calcaneus and plantar fascia. There is a lack of patronization on the literature about how to execute IFM strengthening, nor there is indications of its use for the treatment of PF, isolated or comparing with other gold standard treatments, such as the use of insoles. Objective: To analyze the information regarding the IFM strengthening and its use on the treatment of PF, comparing with foot insoles. Methods: Two Systematic Reviews (SR) were made. The first was to access the adequate training volume to generate changes in the IFM and MLA. The second was to compare the effects of the IFM strengthening training with foot insoles as treatment for PF. Both SR were made following the PRISMA statement, using the PICO strategy. The searching process was carried on the following databases: Cochrane Central, Pubmed, PEDro, LILACS, Scielo, Embase, Cinahl e Science Direct. The inclusion criteria and key words were chosen for with each RS objective. For methodological quality of the selected studies the Cochrane risk of bias table and PEDro scale were applied. Results: Four RCTs were included in the first RS. The IFM strengthening showed increase on the MLA height and medium term, and significant effects on functionality at short term and medium term. For the second RS, three RCTs were included. The resistance training showed more effect for changings in pain and function outcomes. However, there is no sufficient evidence to affirm witch IFM training is the best option. Conclusion: The intrinsic foot muscle strengthening training influences on the medial longitudinal arch height in the medium term and has better dynamic response in the short and medium term. The IMF strengthening can be an alternative to the application of foot insoles on the treatment of PF with satisfactory results for pain.